Penerjemahan Naskah: Problematika dan Solusi - Pudjiastuti, Titik (Jurnal Penerjemahan, 2024)
In Indonesian, a manuscript is also called naskah. Regarding the study of manuscripts, there are three directly related fields, namely codicology, paleography, and philology. Codicology studies the physical aspects of manuscripts, paleography examines the history and development of the script used in manuscripts, and philology discusses the texts contained within manuscripts. The main goal of philology is to reveal the information, functions, and cultural values stored in manuscripts. To achieve this goal, manuscripts must be translated. In this regard, the question arises as to what a manuscript researcher must do to ensure their translation is accurate, accepted, and understood by contemporary society. In the process of translating manuscripts, there are two steps a translator must undertake: transliteration of the text and its translation. A researcher or scholar who serves as a translator must also act as a transliterator of the text. To produce a good manuscript translation, they must possess three skills: they must be familiar with the script used in the manuscript, understand the language used in the manuscript, and have cultural knowledge of the source text's background as well as a broad understanding of current situations to ensure their translation is equivalent in terms of words, phrases, clauses, sentences, and meanings. Keywords: manuscript, transliteration, translation, culture